Phenotypic Manifestations in Two Cases of Osmotic Demyelination Syndrome - Elimam N; Elimam E; Krylova V; Lobanov O; Panteleienko L (International Medical Case Reports Journal)
Noon Elimam,1 Eman Elimam,2 Victoria Krylova,1 Oleg Lobanov,3 Larysa Panteleienko1,4 1Department of Neurology, Bogomolets National Medical University, Kyiv, Ukraine; 2Department of Neurology, Tbilisi State Medical University, Tbilisi, Georgia; 3Department of Neurology, Kyiv City Hospital Number 3, Kyiv, Ukraine; 4Stroke Research Centre, Department of Translational Neuroscience and Stroke, UCL Queen Square Institute of Neurology, London, UKCorrespondence: Noon Elimam, Email noonsiddig@gmail.comAbstract: Osmotic demyelination syndrome (ODS) is an emergency acute neurological condition that usually occurs secondary to rapid correction of chronic hyponatremia (low concentration of sodium in the blood). We present two cases: one with typical ODS following rapid sodium correction, showing classic MRI findings in the pons and basal ganglia; and another with atypical ODS presenting with cranial nerve palsy and ataxia, despite normal sodium levels, and diffuse hyperintensities in the pons and medulla on MRI. These cases emphasize the clinical and radiological variability of ODS, highlighting the importance of careful monitoring and gradual correction of electrolytes, particularly sodium, in high-risk patients.Keywords: osmotic demyelination syndrome, hyponatremia, neurology, neuroimaging